ANALISIS PIDANA TERHADAP PENIPUAN DAN PENGGELAPAN DANA MELALUI M-BANKING DI KOTA MEDAN - Limbong, Daniel; Siahaan, Samuel; Saragih, Feby Yolanda; Zendrato, Elni Puspitasari (Jurnal Ilmiah Advokasi, 2025)
The advancement of digital technology has brought about a significant transformation in the banking sector, particularly through mobile banking (m-banking) services that facilitate various financial transactions. However, this convenience also poses a serious challenge in the form of increasing fraud and embezzlement crimes through the platform. This research aims to analyze the factors causing such crimes in Medan City and evaluate mitigation strategies that can be effectively implemented. The methods used are normative juridical and sociological juridical approaches, with data collection through literature study of laws and regulations, scientific literature, and observation of related social dynamics. The results show that low digital literacy, weak supervision of financial institutions, and the rapid development of technology without the support of an adequate security system are the main factors. In addition, the lack of public understanding of digital risks increases the potential for cybercrime. Therefore, a comprehensive mitigation strategy is needed, including the implementation of multi-factor authentication, strengthening artificial intelligence-based security systems, and continuous digital education. Collaboration between banking institutions, law enforcement officials, government, and the public is key in creating a safe and reliable digital ecosystem.Keywords: Fraud, embezzlement of funds, mobile banking, legal protection, Electronic Information and Transaction Law